Pemanfaatan Screen O Matic untuk Meningkatkan Pemahaman dan Hasil Belajar Kimia di SMA - Sudarsono Sudarsono (Peneliti.net, 2022)
This classroom action research has an aim to improve the learning of Chemistry by applying a media of Sreencast O Matic (SoM) by uploading the resulted material in a platform of Google Classroom (GC). The subject is the science major of Elevent Graders (XI MIPA-1), SMA Negeri 2 Tarakan. They are 35 students. The data were collected by observation, testing and documentation. This inquiry was implemented in two cycles with three learning meetings in each. Based on the analysis, it has been proved that the learning media SoM can be effectively used as learning media and it has improved the students’ learning process and results. These can be seen from their active participation in the learning and their learning achievement. The increase of their learning result indicated 11,4% at the end of first cycle. A dramatic rise of the students’ understanding was proved after the first cycle in which 85,3% of the students have reached more than a minimum completeness of understanding. There were a few of them need a follow up treatment by giving them a remedial.